Successful Thrombolysis after Prolonged Out-Of-Hospital Cardiac Arrest Due to Acute Myocardial Infarction: A Case Report - Lopes, Mariana Pezzute; Bellini, Vanessa Sanches Corcioli; Accorsi, Tarso A. D.; Santis, Antonio de; Magalhães, Francisco Monteiro de Almeida; Minanni, Carlos André; Sou, Jose Leão de (Archives of Clinical and Medical Case Reports, 2020)
Maintenance of high-quality cardiopulmonary resuscitation (CPR) in refractory ventricular fibrillation (VF) and attempted treatment of the underline cause is associated with increased survival in prolonged cardiac arrest (CA). Thrombolysis targeting treatment of presumable acute myocardial infarction during CA, although plausible, is not routinely recommended. However, with the increase in technology to aid diagnosis during cardiac arrest, it is possible to more accurately infer patients who can benefit. This paper is a case report of a patient who presented an out-hospital subtle CA attended promptly by an alone rescuer. Due to geographical and communication conditions, the rescue system was not activated and the patient was transferred to the closer emergency department after 30 minutes of collapse by the rescuer's own means. The patient was resuscitated by a complete team in a satellite emergency unit and monitored with hand-free paddles. The rhythm was recurrent VF and there was rigorous CPR. The electrocardiogram filter showed ST-segment elevation in a short moment of sustained sinus rhythm. Intra-arrest thrombolytic therapy was performed after 25 minutes of in-hospital CA and immediate return to spontaneous circulation (ROSC) observed. Patient underwent cardiac catheterization with angioplasty of the anterior descending coronary and complete neurological recovery. This case report aims to demonstrate the possible effectiveness of thrombolysis during prolonged CA when ST-segment elevation myocardial infarction diagnosis is made by electrocardiogram filter. High-quality CPR and individualization with underlining cause treatment can promote ROSC, neurological recovery and discharge with good quality of life.